My stories, all true : J. David Bamberger on life as an entrepreneur and conservationist - Bamberger, J. David, 1928-; LeBlanc, Pamela A., 1964- (Texas A & M University Press, 2020)
"Bamberger, now in his nineties, tells the story of his life as an entrepreneur and conservationist in his own way in "My Stories, All True." He recounts to journalist and personal friend Pamela LeBlanc how he made a living as a vacuum cleaner salesman, struck it rich as a partner in a wildly successful chain of fried chicken restaurants, and bought, then brought back to life, the "sorriest piece of land" in Blanco County, Texas, the rural oasis he calls Selah, Bamberger Ranch Preserve. In passing along his stories, Bamberger's ultimate goal is to convince people to take responsibility for their actions, to reverse the damage humans have done to the planet, to do the right thing, and to leave the land better than it was when we got here"--Provided by publisher.